STRUKTUR KOMUNITAS VEGETASI MANGROVE DI PESISIR UTARA PULAU MENDANAU DAN PULAU BATU DINDING, KECAMATAN SELAT NASIK KABUPATEN BELITUNG - irma Akhrianti; Franto Franto; Eddy Nurtjahya; Indra Ambalika Syari (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Mendanau Island and Batu Dinding Island are part of small island groups that have a high diversity and density of mangroves. Based on administratively, Mendanau Island is located in the coastal area of Simpang Pesak District, Belitung Regency, which consist of one large island (Mendanau Island) and 1 small island (Batu Dinding Island). The lack of data about potential, diversity, and community structure of mangroves on the north coast of Mendanau Island and Batu Dinding Island, therefore this research is needed as a database for planning, sustainability management of mangroves at the coastal area and small island. The data of mangrove vegetation was taken by purposive sampling method, with using line transect plot (LTP). Ilustration of sampling design is each line transect have 3 plot / kuadratic transect sized 10 m x 10 m (capling), 5 m x 5m (sapling), 1m x 1 m (seedling). The result showed that there are 12 (twelve) mangrove species were found: jenis S. alba, R. apiculata, R. stylosa, R. mucronata, B. gymnorhiza, X. granatum, L. littorea. S. hydrophyllacea, S. taccada, H. tiliaceus, Pandanus, dan I. pes-caprae. Mangrove community structure and mangrove condition on the North Coast of Mendanau Island, at several observation stations, was damaged (poor conditions), while the status of the mangrove conditions on Pulau Batu Dinding was still relatively good